1994
DOI: 10.1007/bf02090381
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatic failure secondary to isoniazid hepatitis with liver transplantation

Abstract: Two patients with liver failure secondary to isoniazid hepatotoxicity were successfully treated with orthotopic liver transplantation. A 49-year-old man received isoniazid prophylaxis for a positive tuberculin test, and a 60-year-old woman was treated for active pulmonary tuberculosis with isoniazid, rifampin, and pyrazinamide. Both patients developed hepatic failure 4 and 1.5 months after initiation of antituberculous drug therapy, respectively. Liver transplantation was performed for progressive hepatic fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…Five of the 8 patients ultimately received transplantation, while the remaining 3 patients died waiting for a donor liver [53]. Farrell et al [54] reported successful liver transplantation in 2 patients. Questions remain regarding the re crudescence rate of tuberculosis after trans plantation in the face of immunosuppression as well as the safety of antitubercular drugs following transplantation if clinically indi cated [54,55],…”
Section: Isoniazid-relatcd Hepatitismentioning
confidence: 99%
“…Five of the 8 patients ultimately received transplantation, while the remaining 3 patients died waiting for a donor liver [53]. Farrell et al [54] reported successful liver transplantation in 2 patients. Questions remain regarding the re crudescence rate of tuberculosis after trans plantation in the face of immunosuppression as well as the safety of antitubercular drugs following transplantation if clinically indi cated [54,55],…”
Section: Isoniazid-relatcd Hepatitismentioning
confidence: 99%
“…Few series of patients have been published about on this issue. Farrell et al (6) report two successfully transplanted cases. One of them was an FHF due to isoniazid chemoprophylaxis, so post-transplant treatment was not needed.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis, hepatic necrosis and death have been described with this drug (5) and the only treatment of fulminant hepatic failure (FHF) is liver transplantation. However, few cases have been published and tuberculosis evolution after transplantation is not very well known (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…10 En caso de lesión hepática grave existen diferentes informes sobre trasplante hepático, llevado a cabo aun con tuberculosis pulmonar activa. 11,12 En EE.UU., la intoxicación por paracetamol es la principal causa de hepatitis fulminante. 13 La toxicidad por isoniacida es la causa de 0,2% de los trasplantes hepáticos pediátricos y del 14% por toxicidad medicamentosa.…”
Section: Falla Hepática Secundaria a Toxicidad Por Tuberculostáticosunclassified